Enhancement of Voltage Stability with Unified Power Flow Controller Considering Loadability Analysis - Yusuf, Samuel Sunday; Okorie, Patrick Ubeh; Abubakar, Adamu Saidu; Momoh, Illiasu Onimisi; Alhassan, Fahad (Journal of Engineering and Technology (JET), 2020)
Voltage stability is an important issue in planning and operation of electric power system during both normal and under contingency conditions. This paper presents line voltage stability index (LVSI) for transmission lines voltage stability assessment and evaluation. The system stability under maximum loading and contingency conditions are analyzed using optimal power flow analysis. FACTS device is considered for a real-time control and a dynamic reactive power compensation of the system. Voltage source-based power injection model of unified power flow controller (UPFC) is used for the minimization of voltage deviation and losses on the network. Optimal location and sizing of UPFC is carried out using grey wolf optimization (GWO) technique in order to identify an optimal location where the FACTS device will be installed. UPFC device has proven to increase the line transmittable power, controls the voltage magnitude at the buses as well as enhancing the stability and security of the power system. The various conditions and scenarios used to test the efficacy of this model for system stability and security under contingency conditions are demonstrated on standard IEEE 14-bus test system.